PENGARUH MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR SISWA KELAS III MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH MUHAMMADIYAH 13 SENDANGAGUNG PACIRAN LAMONGAN - Maftuhah; Vinda Rahma Ifana (STIT Muhammadiyah Paciran Lamongan, 2026)
This study aims to determine the effect of Educaplay media on the learning outcomes of third-grade students in the subject of Akidah Akhlak at Madrasah Ibtidaiyah Muhammadiyah 13 Sendangagung Paciran. This study is a quantitative research that uses a pre-experimental method with a one-group pre-test post-test design. The population in this study consists of all third-grade students of MI Muhammadiyah 13 Sendangagung Paciran Lamongan. The sample in this study consists of all third-grade students, taken using the saturated sampling technique, where all members of the population are taken as the sample. The data collection techniques include observation, pre-test, and post-test. Based on the research results, it shows that the application of Educaplay media has an impact on students' learning outcomes. This can be seen from the calculation of data values in the hypothesis testing using the product moment correlation test on 24 respondents, which shows a significant influence of the Educaplay media on students' learning outcomes in the subject of Akidah Akhlak, with r_xy = 0.906. Meanwhile, for the significance test, the result obtained is t = 10.03, with a significance level of 5% being 2.0739.